THE RELEVANCE OF THE BUGINESE LOCAL WISDOM VALUES TO RELIGIOUS MODERATION - Hamzah Hamzah; Asni Zubair; Satriadi Satriadi (Balai Penelitian dan Pengembangan Agama Makassar, 2023)
This study aims to explore the local wisdom values of the Buginese community regarding Sipakatau, Sipakainge, and Sipakalebbi, manifestations of local wisdom values, and their relevance to religious moderation in Indonesia. This research is classified as qualitative descriptive research with exploratory methods and anthropological approaches. This research was conducted in Mallari Village, Bone Regency, which still has a strong practice of local wisdom and historical values. Data collection was carried out through in-depth interviews, observation, and documentation. The collected data was analyzed, and then the qualitative data were coded for the credibility of the results using the Nvivo-12 software. The results of the study show that (1) the local wisdom values of the Buginese, Sipakatau, Sipakainge, and Sipakalebbi are understood as traditional teachings/noble values, life guidelines, identity and customs that are in line with the Shari'a. (2) The manifestation of Buginese local wisdom values is reflected in people's behaviour by humanizing each other, having good etiquette towards the government, and mutual respect. (3) The relevance of Buginese local values to religious moderation programs lies in the human values of humanizing one another (sipakatau), respecting each other (sipakalebbi), and reminding each other (sipakainge’). The principle of Buginese local wisdom values that as long as they are human beings, it is appropriate to humanize, respect, and remind each other regardless of ethnicity, religion, and race; this is in line with national commitment and tolerance in religious moderation in Indonesia.